Increasing Reading Interest Among Tebel Village Children Through the Micro Library at Riverbanks - Ambarwati, Rita (IAI Darussalam, 2023)
Technology has become an essential thing in the life of every human being, where technology plays a role in supporting all daily activities. This condition impacts children in their infancy or who are sitting in school. The utilization of information technology is seen as not optimal because they prefer to play games and social media rather than explore new knowledge and information, which is very necessary for their educational process. The explanation of the problems above is our reason for holding a literacy program in Tebel Village with children as the primary target. The children who live around the village tend to choose to play with their gadgets rather than read books. Lack of supervision from parents and the influence of the playing environment are some of the contributing factors. The activities increase interest in reading among children through a micro-library program located on the riverbank of Tebel Village. The results of this study were quite successful because more or fewer children had read books. At least, they were a little distracted from the influence of gadgets that had become a part of children’s lives at this time.